Landslide Threat Analysis and Slope Reinforcement Method with Sheet Pile on Singaraja City Boundary Road – Mengwitani Km 37+900 Right - Wirasana, I Made Adi; Sinarta, I Nengah; Armaeni, Ni Komang (Civil and Environmental Science Journal (CIVENSE), 2022)
The trigger factor for landslides is due to high rainfall intensity and long duration and the drainage system on the slopes is not good, causing the soil to become saturated. The Singaraja–Mengwitani City road section every rainy season always occurs landslides due to the geometry of the road adjacent to the slope because it is in a hilly area, as well as a drainage system that does not function during the rainy season. Based on the results of the previous soil investigation, the road section is a type of silty clay due to weathering of the ancient Buyan-Beratan volcanic rocks. The research was conducted through a field investigation with 2 drill points in a depth of 30 m, and slope stability analysis with the help of Geoslope software obtained. The value of the existing slope safety factor was 0.939, while at the time of moderate rain for 6 hours it was obtained SF<0.332, this condition indicates that the slope will fail so that it needs to be strengthened. The reinforcement is carried out with steel sheet piles is 4.49 m with a total length of sheet piles used is 6.49 ~ 7 m, based on the results of the analysis after being given reinforcement of steel sheet piles the safety factor value is 1.674, while when it rains it is moderate for 6 hours at 1,210, the slope is declared stable/safe because SF>1.0.